LEARNERS’ PERCEPTIONS CONSTRUCTION ON ENGLISH BEFORE LEARNING IN KAMPUNG INGGRIS: A SOCIAL CONSTRUCTIVIST STUDY - Muhammad Subhan Fikri; Widyastuti Purbani (ETERNAL (English, Teaching, Learning and Research Journal), 2019)
This paper (1) explores learners’ initial perceptions of English, and (2) explains the development of the perceptions before coming to Kampung Inggris. This paper is based on ethnographic research using interpretivism as a paradigm to understand the learners’ perceptions. The research site was Kampung Inggris TulungRejo village, Pare, Kediri, East Java. The participants were the students in the village. The data were collected through interview. The data were analyzed using iterative model from Miles, Huberman and Saldana (2013). In this model, data condensation, data display and conclusion drawing/verification were used to analyze the data. In the data analysis process, multiple coding and categorizations were used to figure out patterns. The theoretical framework was used in data interpretation. This study found out that (1) the learners’ initial perception on English varied according to their experiences. Most of the perceptions before coming to Kampung Inggris were negative. These perception were affected by the learners’ learning process, the environment and the surrounding people. In the learners’ reality, English was viewed merely on its intrinsic feature. (2) The learners’ perception was developed due to their life experiences. After experiencing some turning points, they believed that English was important for their lives. This change of perception also changed their attitude and became their motivations in learning English in Kampung Inggris.